Designer Drugs for The New Millenium: Gabaa Receptor Subtype Selective Agents - Skonick, Phil (Journal of Basic and Applied Pharmacology, 2015)
Converging lines of evidence indicate that GAB AA receptors are part of the brain’s "biowarning system". For example, dramatic changes in GABAA receptor function precede measurable alterations in the HPA axis following presentation of environmental stimuli. Thus, its is perhaps not surprising that GABAA receptors mediate the actions of the most widely prescribed class of anxiolytic (anti-anxiety) agents, the benzodiazepines (e.g., diazepam). Currently available 1,4-benzodiazepines (as well as other anxiolytics acting through GABAA receptors, such as barbiturates and ethanol) produce other pharmacological actions that may be considered undesirable. Because GABAA receptors are a heterogeneous family of ligand-gated ion channels, the design of subtype selective agents has been proposed as one strategy to produce agents with a more limited range of action (e.g. an anxiolytic lacking sedative properties). Studies in both recombinant and native GABAA receptors clearly demonstrate that the α subunit (that is, α 1à6) is the principal determinant of ligand affinity for a structurally diverse group of compounds acting at allosteric modulatory sites that have traditionally been termed "benzodiazepine receptors". While representatives from several chemical classes (e.g., the imidazopyridine, zolpidem) exhibit selectivity for GABAA receptors containing an a 1 subunit, the pharmacological profiles of these compounds are not dramatically different from "classical" 1,4-benzodiazepines. This may not be viewed as unanticipated, since receptors containing the α1 subunit probably constitute > 50% of the total GABAA receptors pool, and are widely distributed throughout the central nervous system. It can be hypothesized that compounds exhibiting selectivity for GABAA receptor isoforms present in relatively low abundance would possess a more selective range of actions. Based on the reported I 0-15 fold selectivity of Ro 15-4513 for recombinant GABAA receptors containing an a5 subunit (compared to receptors expressing other α subunits), we synthesized a series of novel 8-substituted imidazobenzodiazepines. These compounds possess a marked selectivity (up to 75-fold) for α5 subunitcontaining recombinant and native GABAA receptors. In vivo studies suggest the pharmacological actions of these compounds are mediated through occupation of as containing GABAA receptors. A radiolabelled form of an α5 selective imidazobenzodiazepine ([3H]RY 80) has been used to characterize native and recombinant type GABAA receptors containing as subunits. As had been previously demonstrated for other a subunits, it is likely that amino acid residues proximal to the first transmembrane domain are responsible for the high degree of selectivity of such compounds for GABAA receptors containing an α5 subunits. Molecular modeling studies, together with the use of both mutational analysis and transgenic models should result in as selective agents, prototypic designer drugs for the new millenium.